Interaction of Regional Population and Employment - Wouter Vermeulen; Jos van Ommeren (Tinbergen Institute, 2004)
We investigate the interaction of regional population and employment in a simu1taneousmodel, allowing for interregional commuting. The proposed dynamic specificationdistinguishes between short-run and equilibrium adjustment effects and it encompassesthe lagged-adjustment specification that is standard in the literature. We interpret thelong-run relationship between levels of population and employment as a labour marketequilibrium. The model is estimated on a panel of 1973-2000 annual data for 40regions in The Netherlands, controlling for region and time-specific heterogeneity.Identification of the model is improved by decomposing population growth into netinterregional migration and exogenous natural popu1ation developments. We find thatemployment growth responds quite strongly to deviations from regional labour marketequilibria. Net migration is dominated by housing market developments and in the shortrun on1y slightly affected by increases in regional employment. The main implication isthat equilibrium on regional labour markets is obtained through adjustment ofemployment instead of population. We test and reject the lagged-adjustmentspecification.
Keywords: R11; R23; J23; 330; simultaneous model of regional population and employment; migration; regional labour markets; lagged adjustment dynamics; Regionale Bevölkerungsentwicklung; Regionaler Arbeitsmarkt; Binnenwanderung; Anpassung; Niederlande